Komunikasi Kebijakan dalam Meningkatkan Kepercayaan Publik terhadap Program Makan Bergizi Gratis (MBG) - Muhammad Afriaji (SENTRI: Jurnal Riset Ilmiah, 2026)
Makan Bergizi Gratis Program (MBG) is one of the government’s strategic policies aimed at improving students’ nutritional status and reducing disparities in food access. The success of this program’s implementation is largely determined by the effectiveness of policy communication in building public trust. This study aims to analyze how policy communication strategies contribute to enhancing public acceptance of and trust in the MBG program. The research employs a qualitative-descriptive approach by utilizing literature sources, policy documents, and an analysis of public communication components. The findings indicate that effective policy communication must be grounded in four key principles: group-based transparency, message adaptation to socio-cultural contexts, the involvement of local actors who serve as communication intermediaries, and the effective use of communication media. The Nutrition Fulfillment Service Unit (SPPG), schools, parents, and students as program beneficiaries play essential roles in ensuring that policy messages are delivered accurately, relevantly, and comprehensibly. The communication challenges identified include limited nutrition literacy, potential misinformation, and communication channel gaps in rural areas. In response to these challenges, the study recommends the “3C” communication strategy model: (1) Comprehensive, through the integration of formal and informal communication channels; (2) Contextual, by adjusting messages and media to cultural and geographical characteristics; and (3) Collaborative, by involving multiple stakeholders including SPPG, schools, parents, community leaders, and local media. Overall, the findings demonstrate that effective policy communication can strengthen program legitimacy, enhance community participation, and ensure the sustainability of the MBG program.